2013
DOI: 10.1097/mao.0b013e31827850b8
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Nontraditional Candidates

Abstract: Objective Traditionally, children are cochlear implant (CI) candidates if bilateral severe to profound hearing loss is present and amplification benefit is limited. The current study investigated abilities of adolescents with asymmetric hearing loss (one ear with severe to profound hearing loss and better hearing contralaterally), where the poorer ear received a CI and the better ear maintained amplification. Study Design Within-subject case study Setting Pediatric hospital, outpatient clinic Patients Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…This study suggests that perhaps there are some limitations in improving localization in patients with pre or peri-lingual deafness 21 . A more recent study by Firszt reported 3 of 5 adolescents with unilateral hearing loss had improved speech recognition and sound localiation 28 .…”
Section: Effectiveness Of Cis To Improve Sound Localization and Speecmentioning
confidence: 97%
“…This study suggests that perhaps there are some limitations in improving localization in patients with pre or peri-lingual deafness 21 . A more recent study by Firszt reported 3 of 5 adolescents with unilateral hearing loss had improved speech recognition and sound localiation 28 .…”
Section: Effectiveness Of Cis To Improve Sound Localization and Speecmentioning
confidence: 97%
“…It has been long established that binaural hearing provides improved speech perception, improved localization of sound, increased loudness perception due to binaural summation, and overall improved hearing both in noisy and quiet environments (Cadieux, Firszt, & Reeder, 2013; Ching, van Wanrooy, & Dillon, 2007). Ease of listening has been more recently identified to be a binaural benefit.…”
Section: Advantage To Hearing With Both Earsmentioning
confidence: 99%
“…Even though children with single-sided deafness were not initially recommended cochlear implants due to the hearing in the normalhearing ear being “too good,” implantation has been shown to be successful in children with AHL or UHL (Dwyer, Firszt, & Reeder, 2014; Hassepass et al, 2013). In addition, while not yet considered the standard of care, implant centers are beginning to implant children with AHL, and so far are reporting positive results by implanting the poorer-hearing ear (Cadieux et al, 2013). As previously mentioned, however, instituting speech therapy and IEPs for children with UHL does not completely eliminate the risk of future academic difficulties (J.…”
Section: Advantage To Hearing With Both Earsmentioning
confidence: 99%
“…These studies reveal benefits of bimodal hearing over the use of a cochlear implant alone but continued challenges for listening to speech in noise. Data from some children with better hearing in the non-implanted ear also reveal bimodal improvements in speech perception and spatial hearing that depend on duration of deafness in the poorer ear and access to consistent sound in the better ear 11,12,28,51 . The cohorts of bimodal users represent a very diverse population of implant users 28,5154 .…”
Section: Introductionmentioning
confidence: 96%
“…We thus sought to promote bilateral hearing development by providing the most appropriate device in each ear to our large cohort of children with deafness 7 . A cochlear implant was provided in ears with severe/profound deafness; children with bilateral deafness received two cochlear implants whereas children with better hearing in one ear received one cochlear implant and a hearing aid in the other, better hearing, ear (bimodal hearing) 7,1113 .…”
Section: Introductionmentioning
confidence: 99%